Transforming Occupational Safety and Civil Defense: Wartime Challenges and Solutions - Pogrebnyak, Volodymyr; Kondrat, Oleksandr; Perkun, Iryna; Pogrebnyak, Andrii (Academic journal Industrial Machine Building Civil Engineering, 2025)
This article is dedicated to the urgent need for a fundamental reform of traditional occupational safety and civil defense systems under the conditions of a full-scale war. It examines new, previously unseen risks to the life and health of employees caused by military actions. These threats extend far beyond conventional occupational hazards, including direct missile strikes, the destruction of buildings, cyberattacks, and a severe impact on the mental health of personnel. It is proven that old approaches to occupational safety, which focused on preventing accidents in peacetime, are completely unable to cope with the dynamic, unpredictable, and aggressive nature of military threats. The paper substantiates the urgent need to integrate civil defense measures into the occupational safety management system, transforming two separate systems into a single, holistic, human-centric safety model at the level of each enterprise. Special attention is given to how digital technologies, particularly artificial intelligence (AI), can assist in this process. It demonstrates how AI can predict threats based on the analysis of large volumes of data, automate alert systems, optimize evacuation routes in real time, automatically assess damage, support decision-making in crisis situations, and provide psychological support to personnel. A conceptual model of such an integrated occupational safety and civil defense system, enhanced by AI tools, is proposed. This allows for a shift from a simple reaction to events towards proactive, preventive safety management. Finally, practical and scalable recommendations are formulated for enterprise managers to help them incrementally implement technological innovations into safety processes to increase the resilience and protection of personnel in wartime conditions, even with limited resources.
Keywords: occupational safety; civil defense; martial law; artificial intelligence; predictive analytics; integrated system; psychosocial risks